Comparison of Syntax II Score And Grace Score As Predictors of Major Cardiovascular Events 30 Days after Treatment in STEMI Undergoing PPCI - Abimanyu, Roni; Sitepu, Andika; Nasution, Ali Nafiah (CoinReads Media Prima, 2024)
Introduction: IMA-EST is still the main cause of morbidity and mortality in Coronary Artery Disease (CAD) and PPCI is still the main treatment method for IMA-EST patients. Even though PPCI has been undergone, patients are reported to still experience mortality and morbidity both in hospital and after discharged. The SYNTAX II score uses clinical, laboratory and anatomical parameters that are believed to be better than the GRACE score to predict mortality and morbidity. Method: This study is an observational analytic with a retrospective cohort design in STEMI patients who underwent PPCI at HAM General Hospital from January 2023 to June 2023. Patients who were diagnosed with STEMI and underwent with PPCI had their GRACE score and SYNTAX II score calculated and followed for 30 days. SYNTAX-II Score’s cut-off point, sensitivity and specificity as well as predictive possibilities in predicting adverse outcomes were determined. Then bivariate analysis was carried out on each SYNTAX-II Score and GRACE score. Results: The study subjects totaled 73 people with an average age of 56.05 ± 10.07 years. The incidence of MACE 30 days after treatment in our sample was 23.3%. It was found that the SYNTAX II score could well predict occurrence of MACE 30 days after treatment (cut off 33,75, AUC 0.861; 0.773 – 0.949; sensitivity 94.1%; specificity 69.6%, PPV 94.1% and NPV 67.6). The result of the bivariate analysis of the SYNTAX-II Score were: P < 0,0001; OR: 18,353; 95%; CI: 2,566 – 131,241and the results of the GRACE Score were: P < 0,006; OR 5,854; 95%; CI: 1,442 – 23,764. Conclusion: The SYNTAX II score is better to predict occurrence of MACE 30 days after treatment in STEMI patients who undergoing PPCI compared to the GRACE score.